IMPACT OF CORPORATE GOVERNANCE ON THE COST OF CAPITAL IN INDONESIA WITH NET PROFIT MARGIN AS INTERVENING VARIABLES - Wijaya, Rano; Rini Yayuk Priyati (JWM (JURNAL WAWASAN MANAJEMEN), 2024)
This research was conducted to analysed The Impact of Corporate Governance On the cost of Capital in Indonesia with Net Profit Margin as Intervening Variables in Kompas100 Index Companies on the Indonesia Stock Exchange. The population in this study is the Kompas100 Index Company on Indonesia Stock Exchange (BEI) in 2022. All populations will be used in this research. The data used is secondary data by collecting annual reports of the Kompas100 Index Company on the Indonesia Stock Exchange (BEI) in 2022 (IDX). The results show that Audit Committee Size, Board of Commissioners Size, Company Size, and Debt to Equity Ratio have a significant effect on Net Profit Margin, and Net Profit Margin has a significant effect on Cost of Capital which is calculated using Weight Average Cost of Capital (WACC) on the Kompas100 Index Company listed on the Indonesia Stock Exchange (IDX) for the 2022 period.